Daphnia parasite dynamics across multiple Caullerya epidemics indicate selection against common parasite genotypes - González-Tortuero, Enrique; Rusek, Jakub; Turko, Patrick; Petrusek, Adam; Maayan, Inbar; Piálek, Lubomír; Tellenbach, Christoph; Gießler, Sabine; Spaak, Piet; Wolinska, Justyna (Zoology., 2016)
Studies of parasite population dynamics in natural systems are crucial for our understanding of host-parasite coevolutionary processes. Some field studies have reported that host genotype frequencies in natural populations change over time according to parasite-driven negative frequency-dependent selection. However, the temporal patterns of parasite genotypes have rarely been investigated. Moreover, parasite-driven negative frequency-dependent selection is contingent on the existence of genetic specificity between hosts and parasites. In the present study, the population dynamics and host-genotype specificity of the ichthyosporean Caullerya mesnili, a common endoparasite of Daphnia water fleas, were analysed based on the observed sequence variation in the first internal transcribed spacer (ITS1) of the ribosomal DNA. The Daphnia population of lake Greifensee (Switzerland) was sampled and subjected to parasite screening and host genotyping during C. mesnili epidemics of four consecutive years. The ITS1 of wild-caught C. mesnili-infected Daphnia was sequenced using the 454 pyrosequencing platform. The relative frequencies of C. mesnili ITS1 sequences differed significantly among years: the most abundant C. mesnili ITS1 sequence decreased and rare sequences increased over the course of the study, a pattern consistent with negative frequency-dependent selection. However, only a weak signal of host-genotype specificity between C. mesnili and Daphnia genotypes was detected. Use of cutting edge genomic techniques will allow further investigation of the underlying micro-evolutionary relationships within the Daphnia-C. mesnili system.
Keywords: Daphnia; mezerníky ribozomální DNA; Animals; Host Specificity; Time Factors; selekce (genetika); časové faktory; DNA, Ribosomal Spacer; Genotype; zvířata; Host-Parasite Interactions; Mesomycetozoea; genotyp; interakce hostitele a parazita; hostitelská specificita; Selection, Genetic